Digital Supply Chain Management - New Competitiveness Imperative for Economic Development - Miethlich, Boris; Belotserkovich, Denis; Abasova, Samira; Zatsarinnaya, Elena; Veselitsky, Oleg (International Journal of Supply Chain Management, 2020)
Abstract—The study introduced the concept of countries' digital development in the field of supply chain management (SCM) from the perspective of participation in global supply chains (GSC). A SWOT analysis of the proposed concept was performed, according to which, strengths, weaknesses, opportunities, and threats of the nation's involvement in GSCs were denoted. This research outlined the necessity for creating approaches and programs to ensure the logistics sector's digital growth for developed and developing nations and reduce modern unlevelled threats. The present study statistically verified the hypothesis that the improvement in the country's digital development contributes to the increase in its participation in GSCs. Within the research, indicators that determine the country's digital development in the context of SCM were selected. On their basis, digital profiles of the Russian Federation, Switzerland, Azerbaijan, and Cambodia were created and compared. As a result, the study disclosed competitive strategies in international trade for the countries under consideration. This research presented ways to strengthen the nations' competitive position in the world market and increase their digital competitiveness.